SOLID DISPERSION - A NOVEL APPROACH FOR BIOAVAILABILITY ENHANCEMENT OF POORLY WATER-SOLUBLE DRUGS IN SOLID ORAL DOSAGE FORMS - GUNTAKA, PURNACHANDRA REDDY; LANKALAPALLI, SRINIVAS (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Enhancement of the bioavailability of poorly water-soluble drugs is a challenging task in drug development. Currently 40% of new chemical entities are discovered as poorly water-soluble drugs. Solid dispersion is one of the best technology for improving solubility, dissolution rate, and bioavailability. Solid dispersion techniques are more useful for enhancing drug solubility for a combination of drug and inert carrier to improve wettability, reduced particle size, and converting amorphous particles. This article reviews various advantages, methods of solid dispersions, carriers used in solid dispersion, characterization, and marketed products.